Christmas Grotto As An Art For Experiencing Divine Humility - Yuniarto, Yustinus Joko Wahyu; Maryono, Yohanes; Sari, Maria Dewi Arum; Sari, Maria Dewi Putri (Studia Philosophica et Theologica, 2025)
The installation of a Christmas grotto must begin with a process of meaningful reflection. Without it, such construction may become a hollow and repetitive act. The witness of Scripture must be re-reflected upon so that foundational norms are retrieved, thus ensuring the significance and value of the art continue to offer spiritual benefit to the faithful, and that the art itself maintains its place, is preserved, and passed down. This reflective qualitative study attempts to rearticulate essential Catholic principles that should be present in devotional art surrounding the Christmas Liturgy, so that the artistic expression may be properly and fruitfully carried out. This literature review is grounded in sources considered reliable within Catholic circles. Each source certainly holds varying degrees of influence. We hope this reflection aids readers in reassessing sufficient considerations in realizing devotional Christmas artwork. The key principle to uphold: the Catholic Church uses human art as an auxiliary means to proclaim the Good News in a more beneficial manner for humanity, without obscuring the core message. Therefore, as a means, the Christmas grotto/stall is necessary.